Glycolytic regulation of cell rearrangement in angiogenesis - Bert Cruys; Brian W. Wong; Anna Kuchnio; Dries Verdegem; Anna Rita Cantelmo; Lena-Christin Conradi; Saar Vandekeere; Ann Bouché; Ivo Cornelissen; Stefan Vinckier; Roeland M. H. Merks; Elisabetta Dejana; et al. (Nature Communications, 2016)
Glycolytic regulator PFKFB3 is a key player in vessel sprouting. Here the authors develop a computational model predicting that PFKFB3 drives endothelial cell rearrangement during vessel sprouting by promoting filopodia formation and reducing intercellular adhesion, and empirically validate this prediction.